Nitric Oxide Alleviated High Salt–Induced Cardiomyocyte Apoptosis and Autophagy Independent of Blood Pressure in Rats - Li, Yong; Wu, Xiaoguang; Mao, Yukang; Liu, Chi; Wu, Yiting; Tang, Junzhe; Zhao, Kun; Li, Peng (Frontiers in Cell and Developmental Biology, 2021)
The present study aimed to explore whether high salt diet (HSD) could cause cardiac damage independent of blood pressure, and whether nitric oxide (NO) could alleviate high salt-induced cardiomyocytes apoptosis and autophagy in rats. The rats received 8% HSD in vivo. H9C2 cells or primary neonatal rat cardiomyocytes (NRCM) were treated with sodium chloride (NaCl) in vitro. The levels of cleaved-caspase 3/caspase 3, cleaved-caspase 8/caspase 8, Bax/Bcl2, and LC3 II/I were increased in the heart of HSD rats with hypertension (HTN), hypertension-prone (HP) and hypertension-resistant (HR). Middle and high doses (50 mM and 100 mM) of NaCl increased the level of cleaved-caspase 3/caspase 3, cleaved-caspase 8/caspase 8, Bax/Bcl2, and LC3 II/I in H9C2 cells. The endothelial NO synthase (eNOS) level was increased, but p-eNOS level was reduced in the heart of HSD rats and H9C2 cells treated with 100 mM NaCl. The level of NO was reduced in the serum of HSD rats. NO donor sodium nitroprusside (SNP) reduced the increased levels of cleaved-caspase 3/caspase 3, cleaved-caspase 8/caspase 8, Bax/Bcl2 induced by NaCl (100 mM) in H9C2 cells and NRCM. SNP treatment attenuated the increases of cleaved-caspase 3/caspase 3, Bax/Bcl2, and LC3 II/I in the heart, but had no effect on the blood pressure of HSD rats with HR. These results demonstrated that HSD enhanced cardiac damage independently of blood pressure. Exogenous NO supplementarity could alleviate the high salt-induced apoptosis and autophagy of cardiomyocytes.